Freud e os modelos biológicos de explicação - Martins, Eduardo de Carvalho (2012)
Although Freud has explicitly reclaimed that psychoanalysis belongs to the field of natural science, subsequent philosophic and epistemological criticism tends to refuse the Freudian intention and to place his theories among the human sciences (Habermas, Ricoeur, Schafer, Klein, among others); or to consider it as an unsuccessful naturalistic project, unable to achieve the minimum request of scientificity (Popper, Grünbaum, etc.). In this work we intend to show how several models used by Freud have resulted in different interpretations of psychoanalysis. This thesis is an exegetic study of the explanation models utilized by Freud and the methodological procedure to do it was not only based on his work but also on the contemporary discussion in the field of evolutionary biology whose influences upon Freud have already been indicated by several authors (Sulloway, Ritvo, etc.), although, in general, they only point the presence of biological themes in the elaboration of the Freudian theory, without relating it to a constitution of a psychological explanation model simultaneously historic and naturalistic.